The Role of Housewives’s on Sanitation of Management in Slum Area, Palembang - Odetta Maudy Nuradinda; Hilda Zulkifli; Risfidian Mohadi (Research Centre of Inorganic Materials and Complexs, 2021)
Various environmental health diseases can arise as a result of slum settlements which indicate that environmental sanitation management inadequate and unhealthy, where housewives play an essential role in improving the health status of their families. This study aims to analyze the role of housewives in sanitation management in the slum areas of Palembang, which include the provision of clean water/drinking water, disposal of human waste (feces/latrines), garbage disposal, and wastewater disposal. Sampling method used Non-Probability Sampling with purposive sampling technique. The univariate data analysis technique was then carried out to determine the category level of the role of housewives, including active, participatory, and passive roles. The respondents consisted of 67 housewives from 37th neighbourhood (RT), RT 44, and RT 61 of the Lima Ulu Urban. The analysis of the role of housewives in environmental sanitation management shows a participatory role with a role achievement level of 57%. This role is considered not maximal enough in the management of basic sanitation in their area.